2022
DOI: 10.3389/fenvs.2022.997724
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary game analysis of green technology innovation under the carbon emission trading mechanism

Abstract: The carbon emission trading mechanism is an environmental regulation that has both market and government orientations and has a significant impact on the innovation of green technology and low-carbon development. Based on the evolutionary game theory and considering the strategic choices of different enterprise types in the carbon trading market, a three-party game model, involving enterprise A, the government, and enterprise B, is constructed. Based on data on the carbon emission trading market, data simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…In general, the government provides a subsidy of 500 RMB/ton of standard coal to energy service companies. Through discounting, the subsidy standard for companies carrying out CO 2 emission reduction is set to 200 RMB/ton (Cui et al, 2022). According to the "Ecological Environmental Protection Comprehensive Administrative Law Enforcement Matters Guidance Catalog (2020 Edition)," the penalty for a company's strategic innovation is 2.5 times its subsidy amount;…”
Section: Data Descriptionmentioning
confidence: 99%
“…In general, the government provides a subsidy of 500 RMB/ton of standard coal to energy service companies. Through discounting, the subsidy standard for companies carrying out CO 2 emission reduction is set to 200 RMB/ton (Cui et al, 2022). According to the "Ecological Environmental Protection Comprehensive Administrative Law Enforcement Matters Guidance Catalog (2020 Edition)," the penalty for a company's strategic innovation is 2.5 times its subsidy amount;…”
Section: Data Descriptionmentioning
confidence: 99%
“…The profound logic of carbon emission trading policy is the commercialization, asset, and data of carbon emission rights. By limiting control of enterprise greenhouse gas emissions and emission quotas, with the help of market mechanisms to transform environment negative external cost into enterprise internal production costs, this reverses transmission control to complete the performance conditions, promotes the carbon market to reach the Pareto optimal situation, and finally realizes the quality and efficiency of energy utilization, energy conservation and emission reduction of the whole economy and society [60,61]. An appropriate and reasonably designed environmental regulation policy will promote the constrained individuals to stimulate the consciousness of technological innovation under limited conditions, dynamically integrate the factor input combination, and improve the green total factor productivity [62].…”
Section: The Moderating Effect Of the Carbon Emission Trading Policymentioning
confidence: 99%
“…These two forms of regulation complement each other and demonstrate the involvement of multiple stakeholders in environmental governance. Previous studies have indicated that environmental regulation has both an "innovation compensation effect" [7] and a "compliance cost effect" [8] on GTFP, which yield contrasting impacts. Hence, the question of whether dual environmental regulation Sustainability 2024, 16, 4894 2 of 22 can facilitate the enhancement of GTFP in Chinese urban areas and, if so, the manner in which it may do so, represents a crucial theoretical and practical concern.…”
Section: Introductionmentioning
confidence: 99%